Copper-Catalyzed Synthesis of Weinreb Amides by Oxidative Amidation of Alcohols - Yedage, Subhash L.; Bhanage, Bhalchandra M. (Synthesis, 2015)
A simple and efficient protocol has been developed for the oxidative amidation of alcohols to Weinreb amides using tert-butyl hydroperoxide as an oxidant and an inexpensive and air stable copper catalyst. The present protocol is advantageous as it uses commercially affordable alcohols as starting materials. The developed protocol also tolerates various substituted alcohols as starting materials to provide good to excellent yields of the desired products.
Keywords: alcohol; amide; copper; oxidation; cross-coupling